CONSTRUCTING INTERFAITH HARMONY THROUGH THE DA’WAH OF KH. MAHFUD RIDWAN IN SEMARANG, INDONESIA - Kharis, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2023)
Religious activists or da'i enlighten the mad'u (disciples) to coexist well and peacefully, require tolerant and wise da'wah, and convey the message of Islam as a mercy for all nature. However, the practice of da'wah is often faced with difficulties and obstacles. To overcome these challenges, a person needs to understand the concept of state life that binds all people from various groups and social groups to prevent unexpected societal conflicts. The purpose of this research is to gain a better understanding of the condition of Semarang Regency society before and after KH. Mahfud Ridwan's preaching. In addition, this research will also analyze the role of da'wah in creating inter-religious harmony from 1984 to 2015. This research was conducted in a descriptive qualitative manner using a historical approach. Research data were obtained through observation, interviews, and documentation. The reduction, presentation, and conclusion drawing process was used to analyze the data, and triangulation was used for data validation. The results showed that the condition of the people of Semarang Regency had been better before KH. Mahfud Ridwan's preaching was better afterward. His preaching uses various methods, such as the bil hikmah method, using noble reasoning, wisdom, and a clean heart. Various social and religious organizations, including the NGO Yayasan Desaku Maju, Forum Gedangan, FSUB, and the SOBAT movement, preach based on this bill hikmah. KH also established Edi Mancoro Islamic Boarding School. Mahfud Ridwan benefits the community and forms santri with religious, national, and societal insights. The method of bil mau'idzah hasanah is by holding regular recitations, teaching in pesantren and madrasah, holding seven minutes sermons, and holding activities on Islamic holidays. The bil mujadalah method is used by discussing with people of various religions.